Proses Rebranding MGo Shuttle Menjadi Lintas Shuttle - M. Fauzi Ramadhan; Yanti Setianti; Ade Kadarisman (LUGAS Jurnal Komunikasi, 2019)
MGo Shuttle management decided to rebrand, they changed the overall MGo brand identity. One of them is by changing the name, namely Lintas Shuttle. The company's decision to conduct a rebranding began with the bankruptcy of the parent company, namely PT. Citra Maharlika Nusantara Corpora. finally the son of this holding company, PT. Citra Maharlika Lintas Wahana (CMLW) "Lintas Shuttle" decided to leave and from its parent company. The purpose of this study was to find out why companies rebranded, the process of developing new brands, the new brand management process, the process of evaluating rebranding activities. The method used in this study is descriptive qualitative. Based on the results of the study it can be concluded that the reason for the company rebranding because of the crisis that occurred in the parent company of PT. Citra Maharlika Lintas Wahana and finally decided to break away. The reason for rebranding was also due to misunderstandings regarding the perceptions of employees, and PT. Citra Maharlika Lintas Wahana requires legality after leaving the parent company. Furthermore, the process of developing a new brand is done by changing the company's identity, changes are made to be able to be thought and felt by the customer that the brand that was different from the current one. In the process of managing a new brand PT. Citra Maharlika Lintas Wahana performs management stages by planning (planning) before the activity, in addition to the strategy of delivering messages and promotions in the form of outdoor media, online, sms blast, email blast, and employees. Furthermore, the process of evaluating rebranding activities is carried out by monitoring and controlling activities, this is intended so that when the process takes place, it turns out that there is something that is not appropriate or that there is an addition from the supervisor, it can be directly conveyed.